POSISI SIDE LYING KIRI MENINGKATKAN DURASI TIDUR DAN SATURASI OKSIGEN PADA BAYI BERAT LAHIR RENDAH (BBLR - herlina doloksaribu; Eka Rokhmiati Wahyu Purnamasari; Hari Ghanesia (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2025)
Low birth weight baby as LBW is The baby born weight less than 2500 grams. LBW is The high risk of infection and complication, therefore LBW need intensive care. to find out the effectiveness of left side lying on sleep duration and oxygen saturation in CPAP-installed BBLR in the NICU of Cengkareng Hospital. This study was a quasi-experimental study with a pre and post test with control group design. The population in this study were all CPAP-installed LBW patients in the NICU of Cengkareng Hospital. This study used 2 groups with 15 respondents in each group. The instrument in this study was to fill in the sleep duration and oxygen saturation observation sheet with an oximeter. Analysis using univariate and bivariate using the Mc Namar Test. Based on the results of the study, the P value was 0.016 <0.05, meaning that there was an effect before and after the left side lying intervention on sleep duration in CPAP-installed LBW. research results P value 0.031 < 0.05 means There is an effect before and after the left side lying intervention on oxygen saturation in LBW with CPAP installed. Research results P value 0.250 > 0.05 means There is no effect before and after the supine position on sleep duration in LBW with CPAP installed. Research results P value 1.000 > 0.05 means There is no effect before and after the supine position on oxygen saturation in LBW with CPAP installed